THE CONTENT OF WATER-SOLUBLE VITAMINS IN SUNFLOWER HUSKS AND THEIR APPLICATION POSSIBILITIES IN THE COMPLEX BIOCONVERSION FOR FOOD AND FEED PREPARATIONS - Turgunov Olloyor Ergashali ogli; Khamrakulova Muborak Khakimovna (Western European Studies, 2025)
This study investigates the enrichment of sunflower husks with water-soluble vitamins and assesses their potential applications in the production of functional food and feed supplements. Using High-Performance Liquid Chromatography (HPLC) analysis, sunflower husks were identified as a valuable source of B-group vitamins and ascorbic acid. The findings highlight the high biological activity of these compounds and their suitability for bioconversion processes aimed at enhancing the nutritional value of various food and feed products. Moreover, the research emphasizes the economic and ecological advantages of utilizing sunflower husk-derived bioactive compounds, promoting sustainable resource use and reducing agricultural waste. This work provides a scientific basis for further biotechnological development of plant-derived vitamin complexes for industrial applications
Keywords: sunflower; husks; water-soluble vitamins